No one's waiting: Farmers are driving climate adaptation one solution at a time - Evans, Monica (International Livestock Research Institute, 2025)
In Kenya's Bomet County, farmers Doreen and Edwin Mitey are pushing the frontiers of climate adaptation-and inspiring fellow farmers to do the same. Facing longer dry-season droughts, intense storms, and emerging crop diseases, they have responded with creative, practical solutions. They downsized their herd, shifted from maize to sorghum silage, diversified their crops, harvested more rainwater, and began crossbreeding cows toward adaptive breeds. Their innovations form part of the International Livestock Research Institute's (ILRI) Climate Adaptation Pioneers program, which identifies and supports farmers already developing scalable, locally appropriate solutions through the Pioneer Positive Deviance (P-PD) model. The approach connects farmers through peer learning networks, empowering them to adapt productively to climate change. So far, it has reached over 28,000 households in Kenya, Ethiopia, and Colombia, improving livestock health, feed availability, and resilience-proving that farmers' knowledge can drive lasting climate solutions.